2015
DOI: 10.3390/ijms160510986
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Lipopolysaccharide Results in Myocardial Fibrosis in Rat Offspring

Abstract: The epigenetic plasticity hypothesis indicates that exposure during pregnancy may cause adult-onset disorders, including hypertension, myocardial infarction and heart failure. Moreover, myocardial fibrosis coincides with hypertension, myocardial infarction and heart failure. This study was designed to investigate the effects of prenatal exposure to lipopolysaccharide (LPS) on myocardial fibrosis. The result showed that at six and 16 weeks of age, the LPS-treated offspring exhibited increased collagen synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…There are some limited exploratory studies seeking potential effective preventive strategies during pregnancy or in young offspring by using PIE animal models. We found that pharmacological treatments in the second trimester with PDTC could effectively prevent PIE-programmed hypertension, vascular damage Hao, Zhang, Yuan, et al, 2010), and myocardial remodeling (Chen, et al, 2015;Y. Wei, et al, 2013) in rats.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
See 2 more Smart Citations
“…There are some limited exploratory studies seeking potential effective preventive strategies during pregnancy or in young offspring by using PIE animal models. We found that pharmacological treatments in the second trimester with PDTC could effectively prevent PIE-programmed hypertension, vascular damage Hao, Zhang, Yuan, et al, 2010), and myocardial remodeling (Chen, et al, 2015;Y. Wei, et al, 2013) in rats.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Zhao, Zhang, Cao, Liu, & Li, 2014). In addition, animals that were maternally exposed to LPS or zymosan had increased levels of myocardial fibrosis and myocardial remodeling (Chen, et al, 2015;Y. Wei, et al, 2013), significantly reduced glomerular numbers and creatinine clearance rates, but higher urinary protein levels, indicating renal injury (Hao, Zhang, Yuan, et al, 2010) (Fig.…”
Section: Development Of Experimental Animal Models For Pie-programmedmentioning
confidence: 99%
See 1 more Smart Citation
“…This is interesting as prenatal IL-6 exposure has also been implicated in neurodevelopment and behavioral abnormalities associated with schizophrenia [150]. In addition, injecting the endotoxin LPS to pregnant dams produced diastolic dysfunction [196], associated with cardiac pathological remodeling in the heart involving hypertrophy, fibrosis [197], and apoptosis [196] in the adult offspring. The functional consequence of a prenatal inflammatory environment was impaired diastolic [196] and aortic dysfunction characterized by altered reactivity and connexin expression [198].…”
Section: Prenatal Programming Of Cardiovascular and Autonomic Functionmentioning
confidence: 99%
“…atherosclerosis (aS) is a serious disease that causes hypoxic ischemia of the heart and leads to disordered collagen metabolism during its progression (1,2). Multiple studies have revealed that the urotensin ii/urotensin report (uii/uT) system, which is composed of uii and its receptor, G protein-coupled receptor 14 (GPr14), serves an important role in various diseases, including aS and heart disease (3,4).…”
Section: Introductionmentioning
confidence: 99%